Heterogeneous Exercise Responses to High‐Intensity Interval Training Are Associated With Varied Long‐Term Cardiovascular Outcomes in Patients With Heart Failure: A 15‐Year Follow‐Up - Tieh‐Cheng Fu; Shu‐Chun Huang; Shin‐Sheng Yuan; Chao‐Hung Wang; Jong‐Shyan Wang; Wen‐Chung Tsai; Wen‐Jin Cherng; Yu‐Chiau Shyu; Chih‐Chin Hsu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study investigated exercise response heterogeneity and its mediating role in survival for patients with heart failure. Methods and Results We conducted a retrospective cohort study by examining the registry satabase in 3 institutes from 2009 to 2024. All 182 included patients with heart failure completed 36 sessions of high‐intensity interval training (HIIT) at alternating intensities of 80% and 40% peak oxygen consumption (V˙o2peak). Based on the improvement of V˙o2peak (ΔV˙o2peak=post‐HIIT V˙o2peak−baseline V˙o2peak), they were classified as responders (ΔV˙o2peak>0) or nonresponders (ΔV˙o2peak ≤0). The end points were the long‐term survivals and readmissions for them. The prevalence of nonresponders was 21% (39/182). Responders (n=143) showed significant improvement of oxygen uptake efficiency slope, arteriovenous oxygen difference and skeletal muscle mass after HIIT. The above physiological adaptations in responders were significantly greater than in nonresponders. The 14‐year cardiovascular event‐free survival was significantly better in responders (91.3%) than nonresponders (76.8%). Higher V˙o2peak was a protective factor for cardiovascular death (adjusted hazard ratio [aHR], 0.411 [95% CI, 0.172–0.985]; P=0.046). Male sex (aHR, 0.320 [95% CI, 0.136–0.757]; P=0.009) and higher oxygen uptake efficiency slope (aHR, 0.995 [95% CI, 0.992–0.998]; P=0.005) were protective factors against cardiovascular readmissions. Causal mediation analysis revealed that V˙o2peak mediated the association between HIIT and all‐cause death, while heart rate reserve mediated HIIT effects on cardiovascular readmissions. Conclusions The longitudinal study has identified different physiological adaptations to HIIT in patients with heart failure. Improvement of cardiorespiratory fitness appears to be the dominant factor in reduction of the cardiovascular event for patients with heart failure.